(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Phytochemicals, which are bioactive compounds found in medicinal plants, have been attributed to the therapeutic properties of these plants. Qualitative and quantitative phytochemicals of cold and hot leaf extracts of Rauvolfia vomitoria Afzel were determined using standard methods and GC-MS technique was used to examine specific bioactive constituents. The qualitative results showed the presence of of cardiac glycosides, alkaloids, terpenes, flavonoids, phenols, and tannins whereas phlobatannins, thiols and steroids were absent in the cold and hot leaf extracts. The extract from hot water had a significantly higher (p < 0.05) value in phytochemical content than the cold water in all total phytochemicals determined with flavonoids (4.808 ± 0.099, 2.596 ± 0.045) having the highest concentration in the hot and cold water extract respectively while phenol (1.382 ± 0.010, 1.356 ± 0.002) had the least concentration in the hot and cold water extract respectively. The GC-MS result showed the following: n-Hexadecanoic acid, 9,12-Octadecadienoic acid, methyl ester, (E, E), 11-Octadecenoic acid, methyl ester, Octadecanoic acid, methyl ester, 2-hydroxy-1,3-propanediyl ester, 9-Octadecenamide, (Z), 9-Tetradecenal, (Z), 9-Octadecenoyl chloride, (Z), Tridecanoic acid, methyl ester, n-Hexadecanoic acid, 9,12-Octadecadienoic acid, methyl ester, (E, E), 9-Octadecenoic acid, Octadecanoic acid, methyl ester, etc. The following are a few of the phytochemicals’ pharmacological characteristics: antioxidant, antiviral, anticarcinogenic, antimicrobial, antibiotic, antiallergic and anti-inflammatory. The results of this investigation provide insight into the plant’s medicinal usefulness, especially the hot extract, which had higher levels of phytochemicals. Hence, R. vomitoria plant may be a true source of medicinal agents to manage and treat diseases.